Dynamic Stakeholder Adaptation to Cambride Curriculum Based Learning: Challenges and Strategies - Azzahra Callistadea Valmay; Achmad Supriyanto; Asep Sunandar (Universitas Muhammadiyah Mataram, 2025)
This study aims to analyze the dynamic adaptation of stakeholders to Cambridge curriculum-based learning in elementary schools. It explores stakeholder perspectives, challenges, and adaptation strategies in responding to the unique demands of the Cambridge-based curriculum. The Cambridge curriculum is known for its international approach, emphasizing critical thinking and students' analytical skills. However, its success depends on the effectiveness of learning management in schools. This study uses a qualitative descriptive research method. Data collection techniques include observation and interviews, with data sources obtained from the vice principal of the curriculum section (internal stakeholder) and parents (external stakeholders). The results indicate that implementing the Cambridge curriculum presents challenges for both teachers and students. These challenges must be minimized through strategies applied in schools. Important factors in implementation include framework surgery with combining local and global contexts in learning, granting teacher flexibility in lesson management, conducting supervision, and implementing the English Habits program. This program encourages all school members, especially students, to use English in daily school activities. From these findings, recommendations focus on improving school management and enhancing teacher professionalism. Strengthening teacher training, optimizing curriculum planning, and fostering collaboration among stakeholders are crucial for more effective Cambridge curriculum implementation.